Kajian Mengenai Academic Burnout pada Mahasiswa Fakultas Kedokteran - Della Amelia Juanda; Dewi Rosiana (Bandung Conference Series: Psychology Science, 2024)
Abstract. Academic burnout is a condition of physical, mental, and emotional exhaustion experienced by students due to excessive academic pressure. This term is adapted from the concept of "job burnout," and although students are not workers, the structure of their tasks and exams reflects job-like characteristics that can lead to burnout. Signs of academic burnout include lack of interest, low motivation, and fatigue in completing educational tasks, resulting in demotivation and decreased academic performance. Factors causing academic burnout include workload, control, reward, community, value, and fairness. The main dimensions of academic burnout are emotional exhaustion, cynicism, and reduced professional efficacy. According to research by Syafira et al. (2021), medical students experience academic burnout with high levels of emotional exhaustion in 141 students (44.8%), high levels of depersonalization/cynicism in 166 students (52.7%), and high levels of personal accomplishment in 137 students (43.5%). Rabuka et al. (2023) also revealed that 75.9% of medical students experience academic burnout. Addressing and preventing academic burnout requires attention to proportional workload, emotional support, and a fair and supportive academic environment. Abstrak. Academic burnout merupakan kondisi kelelahan fisik, mental, dan emosional yang dialami mahasiswa akibat tekanan akademik yang berlebihan. Istilah ini diadaptasi dari konsep "job burnout," dan meskipun mahasiswa bukan pekerja, struktur tugas dan ujian mereka mencerminkan karakteristik pekerjaan yang dapat menyebabkan burnout. Tanda-tanda academic burnout mencakup kurangnya minat, rendahnya motivasi, dan kelelahan dalam menyelesaikan tugas-tugas pendidikan, yang berujung pada demotivasi dan penurunan performa akademik. Faktor-faktor penyebab academic burnout meliputi workload, control, reward, community, value dan fairness. Dimensi utama dari academic burnout adalah emotional exhaustion, cynicism, dan reduced professional efficacy. Menurut penelitian Syafira et al. (2021), mahasiswa fakultas kedokteran mengalami academic burnout dengan distribusi dimensi emotional exhaustion tingkat tinggi pada 141 mahasiswa (44.8%), dimensi depersonalization/cynicism tingkat tinggi pada 166 mahasiswa (52.7%), dan dimensi personal accomplishment tingkat tinggi pada 137 mahasiswa (43.5%). Rabuka et al. (2023) juga mengungkapkan bahwa 75.9% mahasiswa fakultas kedokteran mengalami academic burnout. Penanganan dan pencegahan academic burnout memerlukan perhatian terhadap beban kerja yang proporsional, dukungan emosional, serta lingkungan akademik yang adil dan mendukung.